Perancangan Business Plan Toko Sepeda Garuda Bike Shop - Aditya Dumadi; Farda Hasun; Muhammad Iqbal (eProceedings of Engineering, 2016)
There is a change in trend of using bicycles, from transportation to a sport and recreation modes. It also becomes a healthy lifestyle. On the other hand, information technology today is more advanced, pushing business process which initially requires face to face transaction, to a deal using information technology or better known as the online transaction. This basis blazes a business opportunity to sell products of bicycle needs to a wider market. Currently, the apparels and spare parts products in the bicycle market in Indonesia is dominated by imported products. The development of the bicycle market raises some producers who create products locally that has good quality and has its own originality, especially in the apparel product category. Relating it with business opportunity, a store that specialized on selling good quality of apparel products which are made in Indonesia can be a point of difference and an identity of the store. A business plan is needed to run this business idea. The business concept in this research will rely on sales through offline store and online store. This research includes the business concept, feasibility study, and the last is settling a business plan for the business that has been declared as feasible. The analysis result for financial aspect is IDR 561.539.968,- of NPV, 37,142% of IRR, and payback period for 2,263 years. MARR referenced parameter investments at 21.98%. Based on the results, the business is considered as feasible for the financial aspect. The market, technical, and management feasibility, may also be declared as feasible. Business plan was prepared for the store named as Garuda Bike Shop. Keywords: Business plan, Bicycle, Garuda Bike Shop, Feasibility Study, Business plan of Garuda Bike Shop